2014
DOI: 10.1038/nrg3813
|View full text |Cite
|
Sign up to set email alerts
|

A census of human RNA-binding proteins

Abstract: Post-transcriptional gene regulation (PTGR) concerns processes involved in the maturation, transport, stability and translation of coding and non-coding RNAs. RNA-binding proteins (RBPs) and ribonucleoproteins coordinate RNA processing and PTGR. The introduction of large-scale quantitative methods, such as next-generation sequencing and modern protein mass spectrometry, has renewed interest in the investigation of PTGR and the protein factors involved at a systems-biology level. Here, we present a census of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
1,709
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,711 publications
(1,807 citation statements)
references
References 211 publications
15
1,709
1
1
Order By: Relevance
“…The advancement of high-throughput sequencing facilitated the identification of several classes of non-coding RNA species including miRNAs (miRNAs) and a canonical pathway has been established describing the processing and incorporation of these small RNAs into Argonaute-containing complexes [3]. These discoveries have led to a surge in research into exploration of the functional role of post-transcriptional gene regulation within the cell [4]. Here we explore the current state of the art of research into miRNAs and their role in the pancreatic β-cell and how these studies may offer insights into cell types central to the maintenance of energy and glucose homeostasis in the body.…”
Section: Glucose Homeostasis and The Pancreatic β-Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The advancement of high-throughput sequencing facilitated the identification of several classes of non-coding RNA species including miRNAs (miRNAs) and a canonical pathway has been established describing the processing and incorporation of these small RNAs into Argonaute-containing complexes [3]. These discoveries have led to a surge in research into exploration of the functional role of post-transcriptional gene regulation within the cell [4]. Here we explore the current state of the art of research into miRNAs and their role in the pancreatic β-cell and how these studies may offer insights into cell types central to the maintenance of energy and glucose homeostasis in the body.…”
Section: Glucose Homeostasis and The Pancreatic β-Cellmentioning
confidence: 99%
“…While these protocols are currently dependent upon large quantities of source tissue material in cell culture, this limitation excludes the possibility of studying human islets however the development of the stem cell differentiation protocols may make the CLIP protocol viable for human β-cells in the near future. A recent study profiling miRNAs after the immunoprecipitation of Ago proteins revealed stark differences in the small RNA profile suggesting biochemical approaches to profile miRNAs in FACS-sorted human β-cells may provide insight into distinct populations of miRNAs which interact with specific RNA binding proteins [4] [23]. To date, numerous studies have established specific miRNA:target gene interactions implicating the entire range of β-cell physiology and it appears likely that eventually every functional category (i.e.…”
Section: Identification Of Microrna Targets In the β-Cellmentioning
confidence: 99%
“…Although regulation of mRNA transcription has received significant attention in the past, the importance of post-transcriptional control over gene expression has become increasingly apparent in recent years [14]. A multitude of cis- and trans-acting factors exert influence at this level, including those that modulate RNA stability and translation by shortening mRNA poly-adenosine (poly(A)) tails [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Since RNA molecules can have enzymatic activity, and are structurally more versatile than double-stranded DNA, the variety and numbers of proteins binding to RNA is significantly greater than those found associated with classical double-stranded DNA. Accordingly, a multitude of RNA-binding proteins (RBPs) have been described in prokaryotes and eukaryotes [1,2]. RNA binding by these proteins is versatile and is mediated by many different RNA-binding domains (RBDs), which can occur in various combinations within one RBP.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of UV-induced protein-RNA cross-linking, MS has been applied to identify the cross-linked proteins by standard quantitative MS-based proteomic approaches [11][12][13]. Subsequent database-searching has led to the identification of conserved structural motifs in these proteins [2], such as RNA-recognition motifs (RRMs) [14], K homology (KH) domains [15], zinc-finger domains [16], tudor domains [17], double-stranded RNA binding domains (dsRBDs) [18], G-patch domains [19], Sm motifs [20] etc. However, such proteomic approaches yield little or no information about (i) whether the protein cross-links to the RNA through its canonical RBD or through other domains within the protein; (ii) which RBD is involved in interaction with RNA when the proteins contains several potential RBDs; (iii) how proteins that do not harbor any known RBD (as identified by sequence) interact with RNA.…”
Section: Introductionmentioning
confidence: 99%